2009
DOI: 10.1007/s00383-009-2410-2
|View full text |Cite
|
Sign up to set email alerts
|

Locations of osteomyelitis in children with sickle-cell disease at Tokoin teaching hospital (Togo)

Abstract: During examination of sickle-cell children with fever, particular attention must be shown, respectively to the arm, the leg and the thigh, in order to track down quickly, an acute osteomyelitis. Early diagnosis and quick treatment permit to avoid complications and heavy sequela in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…This is a known risk factor owing to its effect on the microvasculature causing bone infarction. The skeletal distribution is similar to that in non-SCD patients, with long bones predominating, 8 but multifocal osteomyelitis is more common. 8,9 Only two articles were specific for osteomyelitis related to SCD, 8,9 although there were several in excluded reviews.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…This is a known risk factor owing to its effect on the microvasculature causing bone infarction. The skeletal distribution is similar to that in non-SCD patients, with long bones predominating, 8 but multifocal osteomyelitis is more common. 8,9 Only two articles were specific for osteomyelitis related to SCD, 8,9 although there were several in excluded reviews.…”
Section: Resultsmentioning
confidence: 55%
“…If an organism is not isolated on culture, the antibiotic chosen should cover both. 8 Symptoms and signs. The clinical features are shown in Table III and vary significantly depending on the site of infection.…”
Section: Resultsmentioning
confidence: 99%
“…13,16 Candida was identified in 1 case in our series. [13][14][15]18,20,21 In contrast, for children without sickle cell disease, the most common location was the wrist (distal ulna or distal radius), which is a rare location (4%). Postoperatively parenteral antibiotic therapy with cephotaxim was continued for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…3 Osteomyelitis of the hand involving phalanges and metacarpals has already been reported in the past in European literature. This location has been found in around 5% of osteoarthritis in patients with sickle cell disease [12][13][14] except in the study by Adeyokunnu and Hendrickse 15 who found an incidence of 19.1%. This location has been reported in the literature but mainly in case reports or in large descriptive studies without a mention of the initial complications and in the absence of long-term follow-up.…”
mentioning
confidence: 90%
“…The most common organism is Staphylococcus aureus followed by Streptococcus pneumoniae and increasingly Kingella kingae [13]. There is an association with Sickle Cell disease due to microvascular infarcts and Salmonella should be considered in these patients [14]. Children present in a similar manner to septic arthritis but may have a prolonged history and more movement of the limb.…”
Section: Osteomyelitismentioning
confidence: 99%